Penerapan Metode Sonikasi terhadap Adsorpsi Fe(III) pada Zeolit Alam Teraktivasi - Rismiarti, Zuri; Yuniati, Yuyun; Alfanaar, Rokiy (ALCHEMY, 2016)
Iron (III) (Fe (III)) is widely used in the industry such us water treatment, the sugar cane, the concrete industry and coal mining. Industrial activity using Fe(III) has potential impact to environmental pollution problems due to that industry produces Fe waste that one of hazardous waste. Fe content excess might toxic effect to human health and the environment. Zeolite as adsorbent has been evaluated extensively for Fe and other heavy metal. Sonication method has been widely developed in polymer preparation. The method is more effective in operation time because the reaction rate increased and also more efficient on the usage of chemical reagens. The optimization of reaction time, the ratio of Fe(III) with activated zeolite, the influence of pH, and temperature has been assessed for Fe(III) adsorption with an activated zeolite by sonication technique. The formation of Fe(III)-SCN complex assay was used for determination of Fe(III) adsorbed by the activated zeolite with using spectrophotometer. The results showed a relatively short operation time (15 minutes), at pH of 4, temperature ofÂ  30 Â°C with the ratio of 1:50 (weight/volume) for the activated zeolite and Fe(III).Â